Pungutan Dana Krama Tamiu Bagi Penduduk Pendatang di Klungkung Bali - Hasan, Hasan (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article highlights the collection of dana krama tamu (migrant ethic fund) for migrants in Klungkung district, Klungkung-Bali Regency. They are borne dana krama tamu by Banjar Adat / Pakraman which is determined by each Banjar Adat / Pakraman. The withdrawal process of dana krama tamu is done monthly by the security guards of Banjar Adat / Pakraman namely pecalang. While the rights that can be obtained by them are security, health care, shelter from disaster, and the use of facilities of Banjar Adat. However, security is not necessarily be felt by all migrants. In the concept of fiqh siyasah (Islamic political jurisprudence), it is unknown about dana krama tamu. But in the history of the Islamic governments, there was a concept of jizya. It is a levie which was taken from ahl al-zimmah as a guarenty for their safety. The collection of dana krama tamu is substantially different withÂ that ofÂ jizya. But there are some similarities that can be seen, especially from the rights given to them. Thus, the withdrawal of dana krama tamu can be justified because it is not much different from the concept of jizya in historical Muslim community.Keywords: Fund levy, Dana Krama Tamu, Islamic political jurisprudence